2023
DOI: 10.1021/acs.jafc.3c03608
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Synthesis, Physicochemical Characterization, and In Silico Studies of Cordycepin-Loaded Bovine Serum Albumin Nanoparticles

Abstract: Cordycepin gets rapidly metabolized in the body into inactive form due to its structural similarity to adenosine, thus inhibiting its development as a medicinal agent. This study was aimed to improve the solubility and stability of cordycepin, a potential drug with known antiproliferative activity, by encapsulating it in bovine serum albumin: β-cyclodextrin nanoparticles. Cordycepin-loaded nanoparticles (CLNPs) were synthesized using the antisolvent method and characterized thoroughly using various techniques.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…These phenomena demonstrated that Myr existed as an amorphous state in the composite hydrogels and further confirmed that Myr was successfully encapsulated. Similar results have also been found when cordycepin was encapsulated in bovine serum albumin nanoparticles . In addition, there were also a handful of weak peaks in the XRD spectra of WPI–Myr and EDP–Myr, which might be because of a tiny amount of Myr present on the surface of the composite hydrogels …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…These phenomena demonstrated that Myr existed as an amorphous state in the composite hydrogels and further confirmed that Myr was successfully encapsulated. Similar results have also been found when cordycepin was encapsulated in bovine serum albumin nanoparticles . In addition, there were also a handful of weak peaks in the XRD spectra of WPI–Myr and EDP–Myr, which might be because of a tiny amount of Myr present on the surface of the composite hydrogels …”
Section: Resultssupporting
confidence: 81%
“…However, these characteristic peaks completely disappeared in the FTIR spectra of protein–Myr hydrogels, indicating that the Myr within protein hydrogels was in an amorphous state. This is because the molecular structure of proteins enshrouded the chemical groups of Myr and shielded its signal representation in the FTIR spectra, thus confirming that Myr was successfully encapsulated into five protein hydrogels . Hydrophobic bonds are usually formed between hydrophobic groups or side chains of protein’s amino acids and play a prominent role in maintaining the stability of protein structure, which can be reflected at around 2900 cm –1 in the FTIR spectra .…”
Section: Resultsmentioning
confidence: 76%
“…These coupling agents can be used to attach a wide range of biological molecules such as proteins, enzymes, DNA, or cells to the surface of the nanomaterials. The resulting NBHs can be tailored for a variety of applications such as tissue engineering, drug delivery, biosensing, medicine, biotechnology, and environmental applications (Jaiswal et al, 2023;Kumari & Samadder, 2022).…”
Section: Ex-situ Synthesismentioning
confidence: 99%
“…Cordycepin, or 3-deoxyadenosine, is a nucleoside analog and the principal active compound found in cordyceps. It possesses various hygienic and pharmacological properties, including antioxidant, antimicrobial, and antiviral activities, as well as immunomodulatory effects [ 1 , 2 , 3 , 4 ]. Moreover, cordycepin has been proven to inhibit adipose accumulation [ 5 ] and exhibit anti-inflammatory and antiproliferative effects on human cancer cells [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%